Neuro-fuzzy and soft computing : a computational approach to learning and machine intelligence / Jyh-Shing Roger Jang, Chuen-Tsai Sun, Eiji Mizutani - Jang, Jyh-Shing Roger
Neuro-Fuzzy and Soft Computing provides the first comprehensive treatment of the constituent methodologies underlying neuro-fuzzy and soft computing, an evolving branch of computational intelligence. The constituent methodologies include fuzzy set theory, neural networks, data clustering techniques, and several stochastic optimization methods that do not require gradient information. In particular, the authors put